UNLOCKING POTENTIAL: SYSTEMS ANALYSIS STRATEGIES TO BOOST MATH SUCCESS IN ENUGU STATE'S POST-PRIMARY SCHOOLS (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
In Enugu state, Nigeria, post-primary education struggles with the low performance in mathematics, which has been brought about by the old-fashioned teaching methods, lack of resources, and indifference on the part of the students. Analytical strategies (SAS) such mathematical modeling, simulation, and optimization, are offered as a new concept to solve these problems allowing to encourage systematic problem-solving and real-life relations. The current article relies on the secondary sources such as educational reports, journal studies, and policy analyses to discuss the issue of what SAS can do to improve the results in math. It identifies the loopholes in the existing practice facilities (involving incomplete training of teachers and insufficient facilities) and shows how SAS encourages a better comprehension and equitable conditions. By using the examples of cases and synthesizing data, the work offers the specialized stages of implementation, which should be applied to Enugu schools with an emphasis on collaboration and integration of technologies. The results indicate that SAS may increase achievement by a maximum of 25 percent, which will lead to new and inclusive approaches to math instruction that are in line with development objectives in Nigeria.